Bridging Gaps in TVET for Learners with Disabilities: Proposed Mental Health, Technology, and Gender Equity Interventions in Coastal Kenya - Anika, A. A.; Mwambia, J.; Muthiani, J.; Wangoli, E. (European Journal of Applied Sciences, 2026)
Learners with disabilities in Technical and Vocational Education and Training (TVET) institutions in Coastal Kenya continue to face multiple challenges that hinder their full participation in learning in order to achieve sustainable development. These include unmet mental health needs, limited access to assistive and digital technologies, and deep-rooted gender inequities. Despite the international and national efforts to inclusive and equitable education, the integration of mental health, technology, and gender remains under-researched in the context of disability-inclusive TVET for the enhancement of learning experiences of learners with disabilities in the Kenyan Coastal region. This qualitative study explores the challenges and recommends coastal context- specific interventions aimed at integrating mental health support, inclusive technologies, and gender-responsive approaches to improve learning outcomes and experiences for learners with disabilities. Data from learners with disabilities, trainers, administrators, parents, and counselors reveal low use of assistive technologies, inadequate mental health services, insufficient training for trainers, and funding constraints. The findings also reveal critical gaps in institutional preparedness, limited mental health support systems, and lack of gender-sensitive frameworks. In conclusion, this study advocates for deliberate collaboration among various stakeholders and sectors grounded in advancing mental health, digital inclusion, and gender equity as a transformative force for empowering TVET institutions in the coastal region for inclusive and gender equitable education. The study generates actionable recommendations for policy makers, educators and development partners to come up with contextually relevant strategies that enable every learner to benefit in the journey towards an inclusive and equitable technical education.